The Analysis of Direct Grant Policy in Covid-19 Pandemic in Justice Perspective - Muhammad Fakhruddin Zuhri; Fenny Bintarawati; Naili Ni'matul Illiyyun; Daud Rismana (Universitas Kuningan, 2021)
The village is a place where people can live side by side in harmony and peace. This what actually has been aspired by our national law long time ago, that is a society which live in equity and prosperous . Laws are made to regulate and bring justice for all elements of the society. This justice should be able to presented by the policy maker and should be realized because it is awaited by all of elements. Especially in the current situation where the COVID-19 pandemic is occuring across the world which is Indonesia state is also affected. Many people, especially the grassroots got the impact of the COVID-19 pandemic, they lost their jobs, that is very meaningful for them to fullfill their daily needs. The Government through the Ministry of Villages, Development of Rural Regions, and Transmigration in the midst of this situation released a program as one of the solution, that is direct grant (Banyuan Langsung Tunai) arranged through the regulation of the Ministry of PDTT Number 6 Year 2020. The research methodology used the qualitative methods which produced descriptive data. The results of this study indicated the BLT policy in the midst of the COVID-19 pandemic is an appropriate solution from the government to help alleviate citizen's living cost especially the burden of rural societies who are affected by COVID-19. The BLT policy in the midst of the 19th pandemic has reflected the sense of justice aspired by the law, because actually a law/regulation/policy was made to create justice for humans, and even that policy became a priority in the context of overcoming the COVID-19 pandemic.ame a priority in the context of overcoming the COVID-19 pandemic.